Need for Regulation of Medical Practice (Hair Transplantation) in India: Delhi High Court (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
This case went before Delhi High Court after the death of a patient who had undergone hair transplant, suffered serious complications. Various medico-legal and ethical issues emerged and need to be felt for the National Protocol for hair transplant in India, as procedure is unregulated by statute, even in Capital of India, Delhi exposing the issue of patient safety. Delhi High Court observed that hair transplantation being an aesthetic surgery needs to be performed by qualified dermatologists or trained surgeons with informed consent of the patient. It is critical to evaluate the risk benefit ratio from the medical perspective. It is imperative on the persons performing the transplantation surgery to be aware of the medico legal issues. Present matter has larger ramifications as number of such treatment Salons are mushrooming, wherein the self-proclaimed technicians are rendering the service of hair transplantation/aesthetic surgery which is completely in teeth of medical ethics and in defiance of standard protocol to be followed for the purpose of hair transplantation/ aesthetic surgery. It appears that in the present case, neither there was informed consent of the deceased, nor the risk involved in the hair transplantation was disclosed to the deceased, which resulted in acute complications finally resulting in the death of the deceased. The case also highlights the issues of medical negligence as well as medical malpractice which continue for want of any check of such Salons by the competent authorities. There is a need for creating awareness among all stakeholders to avoid future deaths in such cases. Concerned government authorities should frame national protocol for hair transplant procedure.
Keywords: Medical ethics; Negligence; Medical malpractice; Hair transplantation; Dermatologist